Asymmetric Dearomative Fluorination of 2‐Naphthols with a Dicarboxylate Phase‐Transfer Catalyst. (4th June 2020) - Egami, Hiromichi; Rouno, Taiki; Niwa, Tomoki; Masuda, Kousuke; Yamashita, Kenji; Hamashima, Yoshitaka
Abstract: A linked dicarboxylate phase‐transfer catalyst enables smooth asymmetric dearomative fluorination of 2‐naphthols with Selectfluor under mild conditions to give the corresponding 1‐fluoronaphthalenone derivatives in a highly enantioselective manner. This reaction, which is compatible with a range of functional groups, is the first example of catalytic asymmetric fluorination of 2‐naphthols, and is expected to be useful in the synthesis of bioactive molecules. Abstract : Not just a phase : A dianionic phase‐transfer catalyst enables fluorinative dearomatization of 2‐naphthols with Selectfluor to afford the fluorinated naphthalenone derivatives in good yield and with high enantioselectivity. This reaction, which is compatible with a range of functional groups, is the first example of catalytic asymmetric fluorination of 2‐naphthols